1997
DOI: 10.1128/cmr.10.4.597
|View full text |Cite
|
Sign up to set email alerts
|

Uses of inorganic hypochlorite (bleach) in health-care facilities

Abstract: Hypochlorite has been used as a disinfectant for more than 100 years. It has many of the properties of an ideal disinfectant, including a broad antimicrobial activity, rapid bactericidal action, reasonable persistence in treated potable water, ease of use, solubility in water, relative stability, relative nontoxicity at use concentrations, no poisonous residuals, no color, no staining, and low cost. The active species is undissociated hypochlorous acid (HOCl). Hypochlorites are lethal to most microbes, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
149
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(154 citation statements)
references
References 143 publications
3
149
0
2
Order By: Relevance
“…As bleach diffuses into the biofilm it reacts with the outermost cells and matrix material, lowering the concentration and therefore leaving little hypochlorite to diffuse farther. These reactions greatly reduce the diffusion rates and is why bleach and other reactive disinfectants are not as effective on biofilms as on planktonic organisms [23,39].…”
Section: Biofilm Resistancementioning
confidence: 98%
“…As bleach diffuses into the biofilm it reacts with the outermost cells and matrix material, lowering the concentration and therefore leaving little hypochlorite to diffuse farther. These reactions greatly reduce the diffusion rates and is why bleach and other reactive disinfectants are not as effective on biofilms as on planktonic organisms [23,39].…”
Section: Biofilm Resistancementioning
confidence: 98%
“…C. difficile spores are stable at temperatures ranging from -20°C to 90°C [35]; they are resistant to desiccation [11•] and are only destroyed by high heat or alkaline pH [36]. A variety of cleaning agents are effective in killing the vegetative forms of C. difficile, but only chlorine-based disinfectants and high concentrations of vaporized hydrogen peroxide have been shown to be sporicidal [37]. In 2000, Mayfield et al [38] demonstrated the superiority of 10% sodium hypochlorite solution (bleach), mixed fresh daily, over quaternary ammonium solution for cleaning the rooms of patients with positive C. difficile toxin tests.…”
Section: Infection Control and Preventive Measuresmentioning
confidence: 99%
“…Up to now, isocyanurates have been chiefly used, besides as sanitizers in the treatment of drinking water and sewage, also in the disinfection of water for swimming pools and industrial cooling towers, in the cleaning of sanitary products, including baby bottles and contact lenses, and in the disinfection of environmental surfaces, of irrigation system for flowers, medical equipment and laundry [21]. The use of chlorine solutions in dentistry deserves a special mention.…”
Section: Introductionmentioning
confidence: 99%